THE EFFECT OF SCROL (SURVEY, CONNECTION, READ, OUTLINE, AND LOOK BACK) STRATEGY ON THE STUDENTS’ READING NARRATIVE TEXT AT GRADE VIII SMP SWASTA PTPN IV BAH JAMBI - Semaria Eva Elita Girsang; Sepwaningsih Silalahi (Program Studi Pendidikan Bahasa Inggris FKIP, 2020)
This study aims to find the effect of the SCROL strategy (survey, relationship, reading, outline, retrospect) on the reading narrative of grade VIII students at PTPN IV Bah Jambi Private Middle School. There are several reference sources used in writing this research journal as well as conducting direct research on class VIII students of PTPN IV Bah Jambi Private Middle School. T.P. 2020/2021. Based on the results of data analysis, it was found that the SCROL strategy (survey, relationship, read, outline, look back) had a beneficial effect in improving students' narrative reading skills on the SCROL strategy (survey, relationship, reading, outline, looking back)